Reperfusion After Fibrinolytic Therapy (RAFT): An open-label, multi-centre, randomised controlled trial of bivalirudin versus heparin in rescue percutaneous coronary intervention. - Amir Faour (Public Library of Science (PLoS), 2021)
Background The safety and efficacy profile of bivalirudin has not been examined in a randomised controlled trial of patients undergoing rescue PCI. Objectives We conducted an open-label, multi-centre, randomised controlled trial to compare bivalirudin with heparin ± glycoprotein IIb/IIIa inhibitors (GPIs) in patients undergoing rescue PCI. Methods Between 2010-2015, we randomly assigned 83 patients undergoing rescue PCI to bivalirudin (n = 42) or heparin ± GPIs (n = 41). The primary safety endpoint was any ACUITY (Acute Catheterization and Urgent Intervention Triage Strategy) bleeding at 90 days. The primary efficacy endpoint was infarct size measured by peak troponin levels as a multiple of the local upper reference limit (Tn/URL). Secondary endpoints included periprocedural change in haemoglobin adjusted for red cells transfused, TIMI (Thrombolysis in Myocardial Infarction) bleeding, ST-segment recovery and infarct size determined by the Selvester QRS score. Results The trial was terminated due to slow recruitment and futility after an interim analysis of 83 patients. The primary safety endpoint occurred in 6 (14%) patients in the bivalirudin group (4.8% GPIs) and 3 (7.3%) in the heparin ± GPIs group (54% GPIs) (risk ratio, 1.95, 95% confidence interval [CI], 0.52-7.3, P = 0.48). Infarct size was similar between the two groups (mean Tn/URL, 730 [±675] for bivalirudin, versus 984 [±1585] for heparin ± GPIs, difference, 254, 95% CI, -283-794, P = 0.86). There was a smaller decrease in the periprocedural haemoglobin level with bivalirudin than heparin ± GPIs (-7.5% [±15] versus -14% [±17], difference, -6.5%, 95% CI, -0.83-14, P = 0.0067). The rate of complete (≥70%) ST-segment recovery post-PCI was higher in patients randomised to heparin ± GPIs compared with bivalirudin. Conclusions Whether bivalirudin compared with heparin ± GPI reduces bleeding in rescue PCI could not be determined. Slow recruitment and futility in the context of lower-than-expected bleeding event rates led to the termination of this trial (ANZCTR.org.au, ACTRN12610000152022).